Melatonina 15 mg pré-operatória para desconforto cirúrgico, dor, edema e trismo em cirurgias de terceiros molares inferiores: ensaio clínico randomizado, duplo-cego e controlado por placebo - Giardini, Carolina Ruppel (Universidade Estadual de Ponta Grossa, 2025)
The extraction of mandibular third molars is a routine procedure widely employed as a clinical model for studying acute inflammatory pain, frequently associated with surgical discomfort, pain, edema, and trismus. Melatonin (N-acetyl-5-methoxytryptamine) is a pleiotropic hormone recognized for its anti-inflammatory properties—through the inhibition of pro-inflammatory cytokines and enzymes such as COX-2 and 5-LOX—as well as for its potent antioxidant activity. Owing to its favorable safety profile and potential analgesic effect, melatonin emerges as a promising therapeutic alternative for managing postoperative complications. This study aimed to evaluate the effects of preoperative administration of 15 mg of melatonin, compared with placebo, on intraoperative discomfort, postoperative pain, edema, and trismus in mandibular third molar surgeries. A randomized, double-blind, placebo-controlled clinical trial was conducted involving 46 patients aged 18 to 26 years, classified as ASA I or II, who underwent third molar extraction. Participants were randomly assigned to receive either 15 mg of sublingual melatonin (n = 22) or placebo (n = 24). Pain tolerance was assessed using a pressure algometer; surgical discomfort was evaluated with the QCirDental questionnaire; pain and edema were measured using a 0–100 Visual Analogue Scale (VAS); and trismus was assessed through self-reporting and interincisal distance measurement on the seventh postoperative day. The sample, predominantly composed of female participants (76%) with a mean age of 21 years, showed no significant differences between groups for any of the evaluated parameters. It is concluded that a single preoperative sublingual dose of 15 mg of melatonin was not superior to placebo, highlighting the need for further studies exploring alternative dosages or formulations.
Keywords: melatonina; terceiro molar; dor pós-operatória; cirurgia bucal; Edema; trismo; melatonin; third molar; postoperative pain; oral surgery; trismus